BIRTH LENGTH AS STUNTING RISK FACTOR IN TODDLERS: A STUDY IN JLEGONG VILLAGE, JEPARA REGENCY, CENTRAL JAVA PROVINCE, INDONESIA - Lisa Jessica; Fx Wikan Indrarto; Suryanto, Yanti Ivana; Zevanya, Evita (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2025)
Stunting is a children growth and development disorder caused by complex interaction of poor nutrition, infection, socio-economic factors, and the absence of adequate environmental stimuli. Stunting incidence in Indonesia is still high, including in Jlegong Village, Keling District, Jepara Regency, Central Java Province, Indonesia. Stunting will impact children’s quality of life, intellectual abilities, health, and productivity which affect the country's economy. The risk factors of stunting are health services, inadequate nutrition, environmental, genetics, and a history of chronic disease. Research about risk factors of stunting has never been carried out in Jlegong village. The aim of this study is to identify risk factors of stunting of toddlers in Jlegong village. The study design was an observational cross-sectional using total sampling. Bivariate analysis was calculated with Chi-square test and multivariate with Fisher's Exact Test. The result showed significant association between birth length with stunting (p-value = 0.001, OR = 19.33). Toddlers who had short birth length (< 50 cm) had 19.33 times higher risk of stunting than toddlers with normal birth length (≥ 50 cm). There was no significant association between birth weight, exclusive breastfeeding, maternal height, frequency of antenatal care visit, the latest level of education of parents with stunting.